An assessment of the relationship between private security companies and the police in crime prevention in Lagos Metropolis, Nigeria - Chinwokwu, Eke Chijioke (International journal of police science & management, 2018)
This study examined the relationship between private security companies (PSCs) and the police during crime prevention in Lagos Metropolis, Nigeria. The study elicited data from 1500 randomly selected respondents to a self-administered survey. Data were further collected through purposive in-depth interviews. Descriptive statistics was used for data analysis. The results showed that operational collaboration and networking between PSCs and the police during crime-prevention strategies in Lagos Metropolis were imperative for achieving a crime-free society. The study shows that PSCs and the police are in a collaborative relationship that has had a positive impact on the reduction in crime; however, synergy between PSCs and the police is weak. The study further found that areas in which PSCs and the police collaborate include: escort duties, static guards, investigation, crowd control and patrol duties. The study also showed that most of the respondents identified areas of future collaboration and improvement between PSCs and the police, including: training, intelligence sharing, investigation and prosecution. The study findings show that both PSCs and the police see their relationship as cordial and complementary, although sometimes unequal and competitive. The study highlights a need to improve interagency collaboration and networking; strengthen collaboration between PSCs and the police; and pool technical resources to fight crime in Lagos Metropolis in particular, and Nigeria in general.